Decision Support System for The Weaning of Rex Rabbit Using Simple Additive Weighting ( SAW ) Method - Asih Pujiastuti; Fachrul Ardiansyah (Compiler, 2019)
Weaning REX rabbits child is one of the keys to success in raising or cultivating rabbits. Unsuitable weaning can result in very high mortality or mortality risks, while weaning for too long results in decreased productivity and the possible marriage of children with rabbit parent. The research done is to design and build the application of decision support system (DSS) with Simple Additive Weighting method (SAW) with 5 criteria as supporting of DSS calculation that are body weight (gram), body length (cm), still breastfeeding or not, already independent for food or not and Gender. The webased DSS application created is tested  by using the calculation system compared with research data. Based on the test of 36 rabbit children which is derived from previous research results obtained showed that the application of the DSS are built 100% the same result.